Handbook of Anticancer Drugs From Marine Origin 2014
DOI: 10.1007/978-3-319-07145-9_27
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets of Anticancer Agents from Filamentous Marine Cyanobacteria

Abstract: The prokaryotic marine cyanobacteria, especially the filamentous forms, are known to produce a plethora of structurally unique natural products. A majority of these molecules are nitrogen-containing, belonging to the hybrid polyketide-polypeptide structural class. Various activities of clinical significance have been attributed to these molecules, ranging from anticancer, neuromodulating to antiprotozoal properties. Particularly in the area of cancer therapy, a number of potent marine cyanobacterial compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Likewise, dolastatin 15, a compound quite similar to dolastatin 10 (addressed in Section 2.5.2 and Section 3.4 herein), demonstrated an effect on growth and differentiation in leukemia cell lines and G 2 /M cell cycle arrest in human myeloma cell lines during in vivo trials [ 149 ]. However, further studies revealed that it was nearly seven times less active than its counterpart [ 140 ]. This slightly weaker in vivo activity was also reported for other molecules such as dolastatin 10 and isodolastatin H [ 248 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, dolastatin 15, a compound quite similar to dolastatin 10 (addressed in Section 2.5.2 and Section 3.4 herein), demonstrated an effect on growth and differentiation in leukemia cell lines and G 2 /M cell cycle arrest in human myeloma cell lines during in vivo trials [ 149 ]. However, further studies revealed that it was nearly seven times less active than its counterpart [ 140 ]. This slightly weaker in vivo activity was also reported for other molecules such as dolastatin 10 and isodolastatin H [ 248 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule–actin interactions are fundamental for many cellular processes such as cell motility, cell division, and cytoskeleton dynamics [ 139 ]. Many depsipeptides derived from bacteria exert activities against microfilaments, causing complete depolymerization of microtubules and hyper-polymerization of actin [ 140 ]. Moreover, they have shown the ability to destabilize microtubules, inducing caspase and Bcl-2 activation, eventually resulting in cell cycle arrest and apoptosis [ 141 ].…”
Section: Depsipeptides With a Recognized Mechanism Of Targeting Cance...mentioning
confidence: 99%
“…General: 1 H and 13 C NMR spectra were recorded on a 400 MHz Bruker NMR spectrometer in CDCl 3 (Cambridge Isotope Laboratories, Inc.), 99.8% D containing 0.03%, v/v, tetramethylsilane (TMS) and residual solvent signal (δ H at 7.26 ppm and δ C at 77.36 ppm) as internal standard. A linear gradient method, used for LCMS data to confirm the absolute stereochemical analysis of the hydrolysate, was carried out with a C 18 RP-HPLC column [Phenomenex Sphereclone 5 µm C 18 (2) 100 Å, 150 x 2.00 mm] using an Agilent 1100 series LC system coupled to a mass selective detector (MSD) ion trap XCT mass spectrometer equipped with an ESI interface system.…”
Section: Methodsmentioning
confidence: 99%
“…Marine cyanobacteria are a rich source of novel bioactive natural products for drug discovery and development [1]. Hantupeptins (1-3) and trungapeptins (4)(5)(6) are cyclic depsipeptides recently isolated from the marine cyanobacterium, Lyngbya majuscula (Figure 1) [2][3][4].…”
mentioning
confidence: 99%
See 1 more Smart Citation